Feeding the soil to feed the planet: soil health outcomes from novel amendments to residue management - Olayemi, Oladapo Peter, author; Wallenstein, Matthew D., advisor; Fonte, Steven J., advisor; Schipanski, Meagan E., committee member; Trivedi, Pankaj T., committee member; Conant, Richard T., committee member (Colorado State University. Libraries, 2021)
Healthy soils are the foundation for the continued capacity of agricultural lands to supply essential ecosystem services while also meeting demands for food, fuel and fiber. From academia to policymakers and other key stakeholders, attention towards soil health continues to rise due to global environmental challenges such as climate change and food security that can be potentially mitigated through the sustainable and innovative management of soils. Specifically, the application of organic inputs including composts and animal manures can help enhance water holding capacity, organic matter accumulation and crop production. However, the heterogeneous nature of soils and diversity of production systems precludes a single ‘silver bullet' solution to optimize soil health. In addition, outstanding questions persist on the differences in spatiotemporal effects of different organic inputs and their application frequency as well as the linkages between different soil health properties. This dissertation examines soil health under two different organic input management regimes including a novel soil amendment derived from cheese manufacturing as well as corn residue management in semi-arid agroecosystems. Both the novel soil amendment and corn residue management approaches were established with the goal of conserving soil water in these water limited systems. The novel soil amendment approach involved the one-time, direct application of a byproduct from cheese production known as lactobionate (LB) to soils through an agronomic trial irrigated with wheat and corn. I found that LB applied to soils increased the water retention capacity as well as the microbial biomass content of soils in the 5-15 cm soil zone under the wheat trial. I also found a non-statistically significant 14% increase in corn yield for LB-amended plots. However, I did not observe any difference in wheat yield and some soil properties (soil pH, soil carbon (C), soil nitrogen (N), and soil ammonium concentration for both trials) with lactobionate addition. My observations suggest the potential for lactobionate to modify soil water content, microbial biomass, nitrate, and yield but outcomes varied by crop trial and amendment rates. This implies that while recycling industrial food processing waste for use as a soil amendment may have benefits for key soil properties, the timing, mode and application rate need to be optimized for maximal effects on soil properties. Due to the effect of LB on soil health observed in the field trials, I conducted an 84-day laboratory incubation experiment to understand specific mechanisms of how LB influences soil organic matter (SOM) decomposition and accumulation via different SOM fractions. I collected soils from the field and split them to add 13C lactobionate to some soils and water only to other soils. I found that about 53% of added lactobionate was respired over 84 days, and observed a positive priming effect after 14 days. In response to LB addition, the total C content of the water extractable organic matter (WEOM) fraction increased by 100% at the initial stage of the incubation but declined exponentially and quicker than other SOM fractions. In addition, the total C content of the light-fraction particulate organic matter (LF-POM) fraction also declined, while both the sand-sized POM and mineral-associated organic (MAOM) C fractions strongly increased relative to unamended control. My results suggest that while lactobionate can help improve soil water retention, it also presents an avenue to building more persistent C through its impacts on the internal cycling of SOM fractions and more importantly on the mineral-associated organic matter fraction considered more relevant to SOC long-term persistence and relative resilience to disturbance. The corn residue management study included a four-treatment combination of residue management (residue retained versus residue harvested) and tillage (no-tillage versus conventional tillage) implemented in the field consistently for 6 years, in contrast to the one-time application of lactobionate. My results showed that the most significant differences across soil properties measured were more apparent at the 0-10 cm zone and were mainly driven by residue retention with minor tillage effects. Regardless of tillage mode employed, retaining residues in the 0-10 cm soil layer led to higher soil water content, soil C, aggregate stability, available phosphate, soil macrofauna and fungal abundance and diversity. Furthermore, residue retention was the main driver of macrofauna and microbial community composition; however, an interaction between tillage and residue management suggested that the effect of tillage on microbial communities was most pronounced when residues were retained. I also found significant covariation between soil physicochemical, macrofauna and microbial datasets, indicating a strong association between different soil properties and cascading effects of management on multiple soil properties. Overall, my findings suggest the impact of both novel amendment and corn residue inputs on soil health varied with application strategy, as the corn residues applied consistently for 6 years had a stronger effect on soil health in the top layer of soils (0 – 15 cm) as compared to lactobionate which was applied one-time. Certain soil properties also responded more quickly to management as compared to others. In addition, while organic inputs are usually applied to target a specific soil health property, other soil health elements can also be affected in a similar magnitude and direction due to latent linkages between different soil properties.